Arbitrary Termination Complex Impedances Tunable Bandpass Filter Using Single and Dual-Mode Resonators - Girdhari Chaudhary; Yongchae Jeong (IEEE Access, 2023)
This paper presents a design of microstrip line tunable bandpass filter (BPF) with a transmission zero (TZ) that can accommodate arbitrarily terminated input and output port impedances ( $Z_{s}$ and $Z_{L}\ne ~50~Ω )$ . We extracted a new coupling matrix to design the proposed tunable BPF and presented an intuitive circuit-level implementation using a single dc-bias controlled single and dual-mode resonators. The proposed tunable BPF integrates the function of tunable filter and matching network into a single circuit. To validate the design, three filter prototypes with different input and output port termination impedances (filter A: 50-to- $50~Ω $ , filter B: 20-to- $50~Ω $ , and filter C: (25+j10)-to- $50~Ω )$ are manufactured and their performances were measured. The experimental results are consistent with the simulation showing that the passband frequency of the BPF can be tuned from 1.65 GHz to 2.08 GHz (23.06%) with the insertion loss variation from 3.40 dB to 4.69 dB. The proposed tunable BPFs achieved frequency selectivity characteristics by locating the TZ at a lower stopband. The proposed arbitrary terminated tunable BPF can allow direct connection between power amplifier (PA)/low noise amplifier (LNA) and antenna without extra matching networks, resulting in smaller circuit size and can enhance overall performance of RF front-end.